Conditions of the foundation of Ukrainian nationalism - Pomarańska, Renata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The consequences of implementing the assumptions of the ideology of Ukrainian nationalism were especially tragic for the Polish population living in Volhynia and Eastern Lesser Poland. The number of Poles murdered by the OUN-UPA and other armed Ukrainian nationalist formations in 1939-1948 is not known exactly, but it is estimated that it was from 80,000 to 150,000 people.
Keywords: Ukrainian nationalism; theory of historical background; theory of civilization